How Should Crowdfunding Research Evolve? A Survey of the Entrepreneurship Theory and Practice Editorial Board. (7th February 2017) - McKenny, Aaron F.; Allison, Thomas H.; Ketchen, David J.; Short, Jeremy C.; Ireland, R. Duane
Abstract : The explosion of crowdfunding within entrepreneurial circles is attracting increased academic interest in the nature of crowdfunding, its antecedents, and its consequences. In an effort to help researchers concentrate their inquiry on the most promising questions and theories involving crowdfunding, we surveyed key thought leaders within the entrepreneurship field—the Entrepreneurship Theory and Practice editorial review board—regarding what inquiry they believe is needed. Their responses offer implications for crowdfunding research. For example, cross‐disciplinary work is one approach that board members believe holds high potential. In response, we outline a cross‐disciplinary research agenda that can inform scholarly efforts.